Does The Birth Order Trigger Speech Delays in Toddler? - - Retnowati, Reni; Rohma, Nikmatur; Eka Yulis Anggraeni, Zuhrotul (Universitas Bondowoso, 2024)
ABSTRACT Background: Genetic factors establish neural pathways for speech understanding in children. Toddlers with fewer siblings score higher in vocabulary development. While reports show birth order's impact on speech development, comparison limitations and inconsistent definitions of variables hinder accurate determination. To better understand birth order's potential impact, factors such as gender, maternal education, and only children should be considered. This study aims to provide new data to clarify the controversy surrounding birth order's effect on speech development. Method: The method was an observational analytics with a cross sectional study method approach to examine the birth order and speech delay. The target population comprised 100 live born children with a gestational age of 28 - 40 weeks in January 2021 - January 2023 in the Maternal Room at Bina Sehat Hospital and lived in Sumbersari sub-district. A Purposive sampling with a judgment sampling method was employed to select a sample of 100 participants. Data collection involved the administration of medical record history anda KPSP Questionnaire in Language section. Data analysis used the non-parametric Spearman Rank correlation test with a significance level of Sig, (2-taled) = 0.05 or p value < 0.05 describes the research design, population, sampling and sampling techniques, and the analytical methods used. Result: The results of research at Bina Sehat Hospital using the Spearman Rank test showed that there was not a relationship between birth order and speech delays in toddler age children (1-3 years) at Bina Sehat Hospital Jember. Conclusion: Based on the results the second birth of children at Bina Sehat Hospital is in large number, the screening rate for speech delays is relatively low and there is a no significant relationship between birth order and speech delays in toddler-aged children (1-3 years) at Bina Sehat Hospital Jember.